Quantitative analysis of nonlinear climate change impact on drought based on the standardized precipitation and evapotranspiration index. (February 2021) - Zhao, Ruxin; Wang, Huixiao; Chen, Ji; Fu, Guobin; Zhan, Chesheng; Yang, Huicai
Graphical abstract: Highlights: A statistic framework and nonlinear detrend method are used in this study. The relative contributions of climate variability on drought are quantified. The dependence of drought trend on climate change varies in region and timescale. Abstract: Exploring the impact of climate change on drought under changing environmental conditions is crucial for agriculture, ecology, and human society. To evaluate the role of climate change on drought, this study selected the Songnen Plain (SNP) in Northeast China as a study area in which to quantify the relative contributions of climatic variables to the drought trend in accordance with the Standardized Precipitation and Evapotranspiration Index (SPEI). A series of SPEI-based numerical experiments, using combinations of observational and nonlinear detrended climatic variable data series, was used as a synthetic approach with which to analyze the relative impact of the individual climatic variables. Results indicated that drought on the SNP has been mitigated marginally during 1961–2016, mainly during spring, winter, the growing season, and on the annual timescale. Significant trends were detected in relation to temperature, sunshine duration, and wind speed, and these variables had differing roles in drought evolution. An increasing trend in temperature was found to aggravate drought tendency at all investigated timescales; however, decreasing trends in net radiation and wind speed offset the drought tendency caused by rising temperature. The positive contribution of wind speed was larger than the negative contribution of temperature, especially in areas around 46°N. Although the change of precipitation was not significant, it promoted drought mitigation on the SNP in spring, winter, the growing season, and on the annual timescale. The analysis framework used in this study was shown useful for improving understanding of the relationship between climate change and drought evolution, and it could prove helpful in providing rational and regulatory policy strategies regarding drought relief.